Stem cell technology for the study and treatment of motor neuron diseases - Lunn, J Simon (2011)
Amyotrophic lateral sclerosis and spinal muscular atrophy are devastating neurodegenerative diseases that lead to the specific loss of motor neurons. Recently, stem cell technologies have been developed for the investigation and treatment of both diseases. Here we discuss the different stem cells currently being studied for mechanistic discovery and therapeutic development, including embryonic, adult and induced pluripotent stem cells. We also present supporting evidence for the utilization of stem cell technology in the treatment of amyotrophic lateral sclerosis and spinal muscular atrophy, and describe key issues that must be considered for the transition of stem cell therapies for motor neuron diseases from bench to bedside. Finally, we discuss the first-in-human Phase I trial currently underway examining the safety and feasibility of intraspinal stem cell injections in amyotrophic lateral sclerosis patients as a foundation for translating stem cell therapies for various neurological diseases.